DETERMINATION OF PERIODICITY OF PREVENTIVE INSPECTIONS OF STAFF BY THE CRITERION OF MAXIMUM EFFICIENCY OF THE OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM - Матиборський, В. В. (Proceedings of National Aviation University (archive), 2021)
The issue of determining the optimal frequency of preventive examinations of workers and employees in the management system of labor protection in accordance with their individualindicators that vary with age.